Time-dependent analysis and representation of force distribution and occlusion contact in the masticatory cycle - Koos, B.; Höller, J.; Schille, C.; Godt, A. (Journal of orofacial orthopedics, 2012)
Objective Until now, the exact timing of force buildup and the distribution of contact points during occlusion have not been analyzed in sufficient detail. Investigations published so far have tended to focus on force curve measurements on single teeth or on a static point in time in the entire dental arch. The objective of this study was to describe precisely and analyze force relations in the dental arch over the course of time and in correlation with their antagonistic dental contact points via instrumental occlusal analysis (T-Scan III; Cumdente, Tübingen, Germany). Materials and methods We assessed 190 masticatory cycles of 38 subjects with 5 repetitions each, analyzing the first 0.15 s after the first recorded antagonistic tooth contact. Recording took place in 0.01-s increments. This measurement method’s precision was positively evaluated in previous studies. Results At t1, 44% of the subjects occluded first in the molar area; surprisingly, while another 40% occluded first on the anterior teeth. Simultaneous initial antagonistic tooth contact occurred in the lateral and anterior teeth in only 16%. At t10 (after 0.1 s), the predominant contact was in the molar and premolar region. The relative masticatory force distribution also changed over time, starting with a relatively large initial force on the central incisors toward the posterior at the recording conclusion. In the lateral comparison (right/left), the force relationships likewise changed over time (t2 on the left 42.6% of the relative masticatory force, 57.4% on the right). By t10, this lateral difference was significantly reduced (47.4% on the left, 52.6% on the right). The lateral difference, thus, decreased by 9.6% from t2 to t10. Conclusion Our data contradict the theory of a simultaneous or even increase in occlusion as the norm. Our detailed analysis of occlusion over time demonstrates that it is the central incisors that usually tend to come into initial contact, perhaps as the result of a guiding function. Over time, the force distribution shifts to the posterior.